PEMBELAJARAN MAHARAH KITABAH BERBASIS COLLABORATIVE LEARNING - Muhammad Fariz; Mukmin Mukmin; Nurul Hidayah (Universitas Islam Negeri Sumatera Utara Medan, 2025)
Arabic language learning comprises four essential skills: listening (istima'), speaking (kalam), reading (qira'ah), and writing (kitabah). Among these, writing is considered the most challenging skill for Indonesian students due to differences in writing systems and grammar structures. This study aims to examine the effectiveness of the Collaborative Learning strategy in improving students' Arabic writing skills (maharah al-kitabah) at MI Marfu'ah Palembang. Using a mixed-methods approach, qualitative data were obtained through observation, interviews, and documentation, while quantitative data were gathered through pre-test and post-test results. The findings reveal that students taught through Collaborative Learning showed significant improvement in writing performance, active participation, and motivation compared to those taught using conventional methods. The study concludes that Collaborative Learning effectively enhances Arabic writing skills and fosters cooperation and responsibility among students